PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH MELALUI CITRA PERUSAHAAN SEBAGAI VARIABEL MEDIASI - Saputra, I Made Deddy; Nurcaya, I Nyoman (E-Jurnal Manajemen; Vol 7 No 12 (2018), 2018)
Customer satisfaction is an important element in determining and maintaining and growing the company. To be able to develop loyalty among its customers, banks need to know what factors influence loyalty and assess their performance in these factors. This research was conducted at PT. BPR Bali Dananiaga Denpasar. The number of respondents of this study were 117 respondents. Data collection is done through observation, interview and questionnaire. This research uses instrument test by using path analysis technique. Based on the analysis result found that service quality variable have positive and significant effect to company image. Quality of service has a positive and significant impact on customer loyalty. So the better the service quality of PT. BPR Bali Dananiaga, it will increase customer loyalty in PT. BPR Bali Dananiaga in Denpasar City. Corporate image has a positive and significant impact on customer loyalty. Corporate image proved able to mediate positively and significantly influence between service quality to customer loyalty.